Reforma al inciso primero del art. 64 de la ley orgánica de servicio público sobre la insercion laboral de personas con discapacidad en el sector público. - Rodríguez Almendáriz, Elina Del Rosario (2014)
This thesis aims at conducting research to present several transformers components to a given problem , that unquestionably falls within the field of social law, promptly within the Public Service Law , is aimed to achieve reform in the legislation , to increase the participation of people with disabilities in the public sector, it has to be in direct proportion to the economically active population , is also aimed at establishing appropriate forms of treatment and get some adjustments aimed at achieving a change in the attitude of these people and the obligation of the public sector institutions to accommodate within it with warmth and appropriate treatment to enable a true labor inclusion without discrimination and marginalization of any kind. The national government through the institutions responsible for social area should be responsible to propose and promote new policies aimed at developing and strengthening the sector through the creation of new instances of induction training and employment for people with disabilities and to create these jobs where they can play with the knowledge acquired in training programs . Disabled people in Ecuador who have greater difficulty moving are less likely to work and most of these people have to face many obstacles being the most common the lack of elevators, ramps and appropriate furniture to perform its functions . It shall be the duty and responsibility of the Ecuadorian State to further systematize the socialization of these issues throughout Ecuadorian society , in order to generate an atmosphere of respect , consideration and confidence in this very important economic and social development of the country group. Maintain an adequate data, aimed at establishing the real needs of employment in this sector, for which be urgent and necessary qualitative and quantitative diagnosis of people with disabilities employed in the public sector , demand from institutions that meet systematic and ongoing reports to be sent to the Ministry of Labour Relations and CONADIS (National Council on Disability ) .